Resistance to cephalosporins and quinolones by Escherichia coli isolated from irrigation water from eastern Lima, Perú - Huamán Iturrizaga, Mónica (2024)
Objetives. Bacterial resistance to antibiotics is a public health problem, however, few studies are performed in natural water ecosystems in middle-low-income countries. The objective of this study was to evaluate the presence and sensitivity to antimicrobials of Escherichia coli strains isolated from 24 irrigation water samples from the Rimac River in eastern Lima. Materials and methods. E.coli were identified by PCR. Antibiotic susceptibility was determined by disk diffusion method. The extended-spectrum beta-lactamase (ESBL), quinolones and virulence involved genes were determined by PCR. Results. All samples exceeded the permissible limits established in the Environmental Quality Standards for vegetable irrigation. Of the 94 strains, 72.3% showed resistance to at least one antibiotic, 24.5% were multidrug-resistant (MDR), and 2.1% were extremely drug resistant. The highest percentages of resistance were observed against nalidixic acid (50%), trimethoprim-sulfamethoxazole (35.5%) and ciprofloxacin (20.4%). Among the isolates, 3.2% presented ESBL phenotype related to blaCTX-M-15 gene. The transferable mechanisms of resistance to quinolones, qnrB were more frequent (20.4%), and 2.04% had the qnrS. It was determined that 5.3% were diarrheagenic E. coli and of these, 60% were enterotoxigenic E. coli, 20% were enteropathogenic E. coli and 20% were enteroaggregative E. coli. Conclusions. Our results show the existence diarrheagenic pathotypes in water used to irrigate fresh produce and highlights the presence of ESBL-producers and MDR E. coli, demonstrating the role that irrigation water plays in disseminating resistance genes in Peru.